2015
DOI: 10.1007/s11684-015-0417-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence chain-based causality identification in herb-induced liver injury: exemplification of a well-known liver-restorative herb Polygonum multiflorum

Abstract: Herbal medicines have recently been recognized as the second most common cause of drug-induced liver injury (DILI) in the United States. However, reliable methods to identify the DILI causality of some herbs, such as Heshouwu (dried root of Polygonum multiflorum), remain lacking. In this study, a total of 12 307 inpatients with liver dysfunction and 147 literature-reported cases of Heshouwu DILI were screened. A general algorithm indicated that only 22.5% (9/40) and 30.6% (45/147) of all hospitalization and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 37 publications
4
85
0
3
Order By: Relevance
“…Despite a significant increase of Heshouwu-induced hepaototoxity has been reported, they occur in a minority of patients in fact by means of the retrospective statistics of medicinal liver injury cases in 302 Hospital, so that they might be idiosyncratic liver injury based on integrated evidence chain-based identification of Chinese herbal medicine (Wang et al, 2015; Zhu et al, 2016). Whereas, the traditional toxicity evaluations showed that Heshouwu treatments caused hepatotoxicity requiring more than 50∼70 times of clinical equivalent dose with continuous administration for 4∼8 weeks (Wang T. et al, 2012; Li et al, 2013; Zhang et al, 2013), resulting in difficult evaluate the hepatotoxicity of herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant increase of Heshouwu-induced hepaototoxity has been reported, they occur in a minority of patients in fact by means of the retrospective statistics of medicinal liver injury cases in 302 Hospital, so that they might be idiosyncratic liver injury based on integrated evidence chain-based identification of Chinese herbal medicine (Wang et al, 2015; Zhu et al, 2016). Whereas, the traditional toxicity evaluations showed that Heshouwu treatments caused hepatotoxicity requiring more than 50∼70 times of clinical equivalent dose with continuous administration for 4∼8 weeks (Wang T. et al, 2012; Li et al, 2013; Zhang et al, 2013), resulting in difficult evaluate the hepatotoxicity of herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Heshouwu has been widely used to prevent hair loss and graying, prevent aging, and extend lifespan, which also has potential for treatment of Parkinson's disease, liver injury, hyperlipidemia, and Alzheimer's disease. However, a typical example of DILI causality determination of Heshouwu was presented by Wang et al [15]. The major active ingredient might be 2,3,5,4 -tetrahydroxy trans-stilbene-2-O--glucoside (TSG), and it was found to expand the lifespan of model organisms by activating Sirtuin 1 (Sirt1) [20,21] and cause autophagy stimulation [22].…”
Section: Current Status Of Hili In Chinamentioning
confidence: 99%
“…Based on the general RUCAM assessment, Wang et al established a model for assessing HILI causality that combines translational laboratory tests with pharmacognosy, phytochemistry, and metabolomics [15,[20][21][22][23] (Figure 1). This model might improve our capability for the diagnosis and causality assessment of HILI.…”
Section: Current Status Of Hili In Chinamentioning
confidence: 99%
See 2 more Smart Citations